Professional Mobility of Student's Youth - Liubomyra Piletska; Tadeush Wawak (Vasyl Stefanyk Precarpathian National University, 2017)
The problem is in the sense of professional mobility not only as a process of retraining or adaptation to the profession, as well as continuous personal self-development, transition to another stage career and the acquisition of new social and psychological competences. We considered professional mobility as the foundation a basis of effective response of the personality to the "call" of modern society, the peculiar personal resource which is the cornerstone of effective transformation of public environment and itself in it; the system multilevel phenomenon that requires the integrated, cross-disciplinary approach to the research; internal (motivational and intellectual and strong-willed) potential of the personality, the cornerstone of flexible orientation and activity reaction in dynamic social and professional conditions according to own living positions; provides readiness for changes and realization of this readiness in the activity (readiness of the personality for modern life with his multidimensional factors of the choice) determines professional activity, subjectivity, the creative relation to professional activity, personal development, promotes the effective solution of professional problems. In professional mobility of young students it is important to consider the socio-economic aspects.